Optimalisasi Strategi Pembelajaran Bahasa Inggris Melalui Penguatan Karakter Mulia - Yusaeny Rozelyna (Jurnal Didaktika Pendidikan Dasar, 2023)
21st century English learning refers to communicative, intercultural competencies, attitudes in the form of self-confidence to be independent and responsible, as well as critical and creative reasoning skills. Creative and interesting digital learning has not been able to reflect the expected English learning achievement targets. This study describes the effectiveness of strengthening noble characters towards optimizing English learning. Classroom Action Research (CAR) using simple qualitative and quantitative methods is used to answer the formulation of this research problem. Observations of students and teachers in the learning process, questionnaires, interviews and documentation of grades were used to collect research data. Researchers use cognitive diagnostic assessment as a preliminary study of research. Observation data of students and teachers are used to answer the optimization of the English learning process. To answer the strengthening of character education in the learning process, the researchers used questionnaire data. Furthermore, interview data after the learning process, documentation of process values and results were used as data triangulation to achieve research validity. Interestingly, this study has a novel value, namely, character strengthening carried out in the English learning process is able to increase the positive behavior of students who are sustainable in the formation of noble character. The increase in the value of the learning process is an implication of changes in the positive behavior of students. Finally, the researcher recommends future research to examine the effectiveness of the text-based approach in cognate subjects.